P-glikoproteien neutraliseringspotensiaal en weefsel verspreiding van tetrametiel-piperidien derivate van klofasimien (Afrikaans) - Medlen, Connie E. (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2010.